A Study on the Nondestructive Evaluation of Carbon/Carbon Brake Disks Using Infrared Thermography. Issue 3 (March 2014) - Shin, Hee Jae; Cha, In Pyo; Lee, Min Sang; Ko, Sun Ho; Kim, Hong Gun; Kwac, Lee Ku
Carbon/carbon brake disks that use carbon fibers impregnated in a carbon matrix are widely utilized in aircrafts and automobiles owing to their high strength, high heat conductivity, low density, and excellent overall mechanical properties. Carbon/carbon brake disks are high cost products and require multi-process manufacturing. The safety and material efficiency of defective products reduces significantly and nondestructive testing is required to monitor the quality, homogeneity, and integrity of the material. In general, radiographic evaluations pose safety problems owing to the use of radiation in such evaluations and ultrasonic flaw detection is difficult to use because of its dependence on the surface of the specimen. This study uses an infrared thermography camera technique, which is not influenced by the sample surface, to monitor the heterogeneity of materials during the manufacturing process and to thus prove the reliability of the method.